UTICAJ FIZIČKE AKTIVNOSTI NA KVALITET KOSTI - Đorđe Bajić; Nela Rašeta; Nenad Ponorac; Zorislava Bajić (University of Banja Luka, Faculty of physical education and sport, 2010)
A bone is a dynamic tissue that remodels during the entire life span. Remodeling includes twocontinuous processes, namely forming and resorbing. These processes are continuous and occur asa response to a weight-bearing physical activity. Remodeling processes are very important formaintenace of skeletal homeostasis.Recent evidence shows that growing bone is more responsive to mechanical loading and physicalactivity then mature bone. This indicates that regular exercise early in life may be an importantfactor in the prevention of osteoporosis later on.Further, high and medium level of weight-bearing physical activity (walking, ball games, dancing,aerobics, jogging, skiing, martial art, gymnastics, strength training and racket sports) correlatespositively with the high bone mass in adults. For elderly even an hour of slow walking (low level ofactivity) can have a beneficial effect on the bone quality.Research done on athletes shows that they have higher bone mass than non-athletes and that thebone density increases during the periods of intensive training.Weight-bearing physical activity is essential for normal development and maintenance of healthyskeleton.In humans, physical activity appears to play an important role in maximizing bone mass duringchildhood and the early adult years, maintaining bone mass through the fifth decade, attenuatingbone loss with aging, and reducing falls and fractures in the elderly.